2019
DOI: 10.1016/j.anr.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Multicomponent Cognitive Stimulation Program on Cognitive Function Improvement Among Elderly Women

Abstract: This study was conducted to identify the effect of a multicomponent cognitive stimulation program (MCSP) on the improvement of older people's cognitive abilities. It also aimed to determine whether the effectiveness of the MCSP is related to age. Methods: A one-group pretest-posttest design was used. The program was conducted once a week for 10 weeks. The Korean-Montreal Cognitive Assessment (K-MoCA) was used to measure cognitive functions before and after the MCSP. Participants included 37 people aged over 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…However, we have identified only few studies that analyzed the effect of these programs on the cognitive subdomain of language. The study by Park et al [40] also found significant differences in language skills with a similar number of sessions to our study, but with a pretest-posttest design and a multicomponent program. Regarding verbal fluency, we have identified three studies whose results agree with those obtained in our study: the global cognitive improvement in MMSE and the improvement of verbal fluency, with similar programs that work comprehensively on cognitive functions [37,45,49].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, we have identified only few studies that analyzed the effect of these programs on the cognitive subdomain of language. The study by Park et al [40] also found significant differences in language skills with a similar number of sessions to our study, but with a pretest-posttest design and a multicomponent program. Regarding verbal fluency, we have identified three studies whose results agree with those obtained in our study: the global cognitive improvement in MMSE and the improvement of verbal fluency, with similar programs that work comprehensively on cognitive functions [37,45,49].…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, other studies have shown cognitive benefits with different techniques in healthy older adults, regardless of their initial cognitive status [35][36][37][38][39][40][41][42][43][44][45]. This reflects a general view that lack of cognitive activity accelerates cognitive decline [46] and that cognitive stimulation could optimize cognitive function [47,48] producing an increase in neuronal volume [49].…”
Section: Discussionmentioning
confidence: 76%
“…Regarding global cognition, the personalized and adapted program of CS achieved statistical significance between and within group improvements in the ND, SCI, and LD groups, post-intervention, and at months, and 12 months. Other authors found similar results between groups in participants with normal cognition (Polito et al, 2015;Schultheisz et al, 2018) and within group (P. Gamito et al, 2020;Park et al, 2019;Tarnanas et al, 2014); in participants with MCI bet-ween groups (Polito et al, 2015;Tsai et al, 2019), and within group (Llanero Luque et al, 2011), also including older adults from MCI to mild-to-moderate dementia bet-ween groups (J Alves et al, 2014) and within group (Kim et al, 2017) post-intervention; as well as an effect of interaction between session and group in participants with MCI (Moro et al, 2015) In agreement with our results, other authors also found no significant differences in participants with dementia, between groups (Capotosto et al, 2017;Liu et al, 2021;López et al, 2022), all of them administered adapted CS but with a higher number of sessions. Two of them applied participants living in a community and within group (Alvares-Pereira et al, 2021;J Alves et al, 2014;Capotosto et al, 2017;Cove et al, 2014;Gibbor et al, 2021;Justo-Henriques et al, 2021;López et al, 2022;Miranda-Castillo et al, 2013;Orrell et al, 2012;Orgeta et al, 2015), four of these studies applied to in younger aged older adults (J Alves et al, 2014;Cove et al, 2014;Justo-Henriques et al, 2021;Orgeta et al, 2015), and five administered adapted CS (Jorge Alves et al, 2014;Capotosto et al, 2017;Cove et al, 2014;Gibbor et al, 2021;…”
Section: Discussionsupporting
confidence: 54%
“…Regarding the cognitive language domain, we obtained improvement even though language skills decrease with age [ 80 , 81 ] and SMC patients have lower scores on fluency tests [ 10 ]. Other studies also find linguistic improvement but with multi-component programmes [ 52 , 66 , 82 , 83 ] compared to our multi-domain programme specifically focused on the language domain.…”
Section: Discussionmentioning
confidence: 51%